Clinical characteristics of cutaneous lupus erythematosus - Szczęch, Justyna; Rutka, Maja; Samotij, Dominik; Zalewska, Agnieszka; Reich, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Lupus erythematosus (LE) shows a wide variety of clinical manifestations, skin involvement being one of the most important. Aim : To analyze the clinical presentation of cutaneous variants of lupus erythematosus in terms of skin lesion spectrum and extracutaneous involvement. Material and methods : A total of 64 patients with cutaneous LE (CLE) were included. The study was based on the “Core Set Questionnaire” developed by the European Society of Cutaneous Lupus Erythematosus (EUSCLE). Clinical severity of skin lesions was evaluated with the Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI). All results were subjected to statistical analysis. Results : Fifteen (23.4%) patients had an acute CLE (ACLE), 26 (40.6%) subacute CLE (SCLE) and 21 (32.8%) chronic CLE (CCLE). Two (3.2%) individuals only demonstrated urticarial vasculitis as a cutaneous manifestation of LE and these patients were excluded. Patients with ACLE were characterized by the earliest onset of the disease (mean age of 31.9 ±15.0 years; p < 0.001). On average, 4.8 ±1.8 criteria of systemic LE were found in the ACLE group compared to 2.7 ±1.3 criteria in SCLE and 2.5 ±1.5 criteria in CCLE (p < 0.001). The highest activity of skin lesions according to CLASI was found in the SCLE group (p = 0.002). On the other hand, the most severe skin damage was observed in CCLE (p < 0.01). Conclusions : Each variant of CLE differs significantly from the others in respect of various aspects of clinical manifestations. Due to a number of different variants of LE skin lesions, a unified classification of CLE still remains a challenge.